Production Performance of Broiler Chickens in Closed House Farms in Peusangan Siblah Krueng District, Bireuen Regency, Aceh - Aqila, Alifa; Risna, Yayuk Kurnia; Adam, Koji Al (Journal of Tropical Animal Science and Technology, 2025)
This study aims to evaluate the value of feed consumption, feed conversion and weight gain of broiler chickens kept in closed house cages for 28 days. This research was carried out on a broiler chicken farm in Pante Baro Buket Panyang Village, Peusangan District, Bireuen Regency with a capacity of 11,000 heads of the Lohman MB 202 strain. This research used descriptive methods with observation techniques. The research variables are body weight gain, ration consumption, ration conversion and performance index. The results of the study showed that rearing broiler chickens in closed house cages for 28 days could increase body weight gain by 1,538 g/head ± 607.54, feed consumption by 2,442.9 g/head ± 966.15, feed conversion by 1.59 ± 0.11, the cage temperature ranges from 25°C-30°C and the standard performance index is 338. It can be concluded that keeping broiler chickens in cages closed house for 28 days in the good category.